Restorative Justice and Peace Creation in Western Kenya - WANDA Ronald Elly (Ученые записки Института Африки Российской академии наук)
The article assesses the use of indigenous methods of conflict resolution embedded in restorative practices and seeks to establish the role that Mount Elgon’s Residents Association played in peace-building in the area. The study adopts the theoretical work of Johan Galtung’s conflict analysis model and John Paul Lederach’s conflict transformation work on peace-building. The study reveals a yawning need for younger community members to be more involved in peace-building activities in the Mt Elgon area. It further reveals that community members aged between 35 and 54 years strongly believe that their traditional culture and indigenous practices is central to their peace-building efforts in their locality. The study found out that a majority of community members felt that their involvement has played an important role in disarming local militia groups and in peace-building. Overall, the community strongly pointed at land and “dirty politics” as issues being at the forefront of community conflict in Mt. Elgon.